University of Central Florida Takes the Bronze at Annual International Programming Competition. - Buzzelli, Timothy (Computer (00189162), 2018)
Three programming team members from the University of Central Florida traveled across the world to compete in the ACM International Collegiate Programming Contest World Finals, ultimately earning the bronze medal. Team member Timothy Buzzelli reflects on his World Finals journey and the training and guidance that led to victory.